The Effectiveness of Implementation of Electronic Integrated Mortgage Transparency through Digital Archive Management - Murdiningrum, Nurmawati (TABELLIUS: Journal of Law, 2023)
The aims of this study were: (1) to find out and analyze the effectiveness of implementing electronically integrated mortgage transparency through digital archive management at the National Land Agency of Salatiga City; (2) to find out the obstacles faced by the Salatiga City National Land Agency in implementing transparency of electronic integrated mortgage rights through digital archive management and solutions. The approach used is sociological juridical. The results of the study conclude that: (1) HT-el services are more effective than conventional HT services, because they can be carried out online, so that users, namely creditors (Banks) or Notaries (PPAT) do not have to come to the local BPN Office to take care of Mortgage Rights, and HT-el application data is stored in a database to facilitate the document search process, and electronic documents (HK-el) have the same legal force as printed documents; (2) Obstacles encountered in HT-el services can be caused by internal factors (reliability of the BPN computer network system to serve HT-el) and external factors (user capacity in operating HT-el computer networks). Keywords: Digital; Electronic; Integrated; Mortgage; Transparency.